Siyāqiyyah Interpretation of the Word Nūr in QS al-Nūr (24):35: A Comprehensive Linguistic Analysis of Phonology, Morphology, Syntax, Collocation, and Rhetorical Style - sri wahyuni; Alvin Ziaulchoir El Nasair; Rexza Mohammad Aufi; Nur Hasaniah (UIN Kiai Haji Achmad Siddiq Jember, 2026)
The word nūr in QS An-Nūr:35 contains deep symbolism that metaphorically represents divine guidance. The relevance of this topic lies in the need for a comprehensive linguistic approach to understand the meaning of nūr not only literally, but also in the context of the structure of the verse and the theme of the surah. This study aims to interpret the term nūr comprehensively through linguistic-siyāqiyah analysis, covering aspects of phonology, morphology, syntax, collocation, and style. The method used is descriptive-analytical qualitative with a classical approach to ma‘ani, bayān, and badī‘ theory. The primary data is the text of QS An-Nūr:35 from the Uthmani Mushaf, and secondary data is obtained from classical tafsir and contemporary linguistic studies. Data collection techniques through literature study and analysis are carried out using source triangulation. The results of this study indicate that the long vowel sound nūr reinforces spiritual meaning; the morphological form mashdar suggests the eternity of meaning; the syntactic structure forms a progressive visual narrative; collocation presents a network of layered meanings; and the style of language constructs complex metaphors that describe light as divine guidance. This study shows that nūr is not merely a symbol of light, but a principle of spiritual guidance that underpins the social ethical system and human faith. These findings enrich the linguistic interpretation of the Qur'an and emphasise the importance of the siyaqiyah approach in understanding the transcendental message of revelation.